Un diálogo difícil con los contemporaneístas - Eduardo González Calleja (Les Cahiers de Framespa)
Bartolomé Bennassar maintained a stormy relationship with contemporary Spanish history, where alternated editorial successes such as his Historia de los españoles, failures such as Le défi espagnol and controversies such as those raised by his biography of Franco and his essay on the Civil War. His historiographic perspective was influenced both by the social and geographical environment he frequented (the most conservative Castile, one of the Spanish regions less prone to change in a modernizing sense) and by his thematic preferences, which were aimed at the study of collective mentalities in the long-term, characteristic of the renewal impulse of the Nouvelle Histoire. Hence, their political analysis, inevitably conditioned by short-term factors (whose impact was evident in the vertiginous thirties), are controversial, despite their desire, so often proclaimed, of balance and impartiality in the analysis.